2015
DOI: 10.1007/s13277-015-3163-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of peptide regions of SERPINA1 and ENOSF1 and their protein expression as potential serum biomarkers for gastric cancer

Abstract: This study aimed to detect potential serum biomarkers for gastric cancer. In the present study, we used magnetic bead-based purification and matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry to detect potential serum markers in 70 gastric cancer (GC) patients compared with 72 healthy controls. On average, up to 81 peaks, of which 11 were significantly different m/z peaks (fold change >1.5; P < 0.001, Wilcoxon rank sum test) between GC group and healthy controls were detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
4
14
0
Order By: Relevance
“…Ovarian-cancer-specific peptides and/or phosphopeptides from cellular proteins, membrane proteins, nucleic acid binding proteins, signaling factors, metabolic enzymes and others including uncharacterized proteins showed significantly greater observation frequency. In agreement with the literature, peptides from many common proteins including acute phase response proteins such as Haptoglobin (HP) [39], Haptoglobin Related Protein (HPR), Alpha Anti Trypsin (SERPINA1) [15] and others were more frequently observed in ovarian cancer samples [38] (Table 1). The Chi Square analysis showed some proteins with χ 2 values that were apparently far too large (χ 2 ≥ 60, p < 0.0001, df 1) to all have resulted from random sampling error (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Ovarian-cancer-specific peptides and/or phosphopeptides from cellular proteins, membrane proteins, nucleic acid binding proteins, signaling factors, metabolic enzymes and others including uncharacterized proteins showed significantly greater observation frequency. In agreement with the literature, peptides from many common proteins including acute phase response proteins such as Haptoglobin (HP) [39], Haptoglobin Related Protein (HPR), Alpha Anti Trypsin (SERPINA1) [15] and others were more frequently observed in ovarian cancer samples [38] (Table 1). The Chi Square analysis showed some proteins with χ 2 values that were apparently far too large (χ 2 ≥ 60, p < 0.0001, df 1) to all have resulted from random sampling error (Fig.…”
Section: Resultssupporting
confidence: 81%
“…High expression of SERPINA1 has been observed in prostate (55), lung (55) and colorectal (18) cancer. SERPINA1 was also reported to be upregulated in serum samples of patients with gastric cancer compared with healthy individuals (56). The present study demonstrated that SERPINA1 was overexpressed in colorectal, esophageal, gastric and pancreatic cancer, which indicated a strong association between a high SERPINA1 mRNA levels and digestive system tumorigenesis.…”
Section: Discussionsupporting
confidence: 62%
“…According to PANTHER Classification System, the protein encoded by SERPINA1 is a serine protease inhibitor involved in endopeptidase inhibitor activity, protease binding and serine-type endopeptidase activity. Higher levels of SERPINA1 has been associated with chemoresistance of human epithelial ovarian cancer [72] and breast cancer [73] and has also been proposed as a potential serum biomarker for GC [74]. However, the role of SERPINA1 in resistance to CDDP in GC has not been clarified yet.…”
Section: Discussionmentioning
confidence: 99%